Platelet Reactivity Is Independent of Left Atrial Wall Deformation in Patients with Atrial Fibrillation - Nathan Procter; Vincent Goh; Gnanadevan Mahadevan; Simon Stewart; John Horowitz (Mediators of Inflammation)
It has been documented recently that left atrial (LA) deformation in AF patients (while in AF) is predictive of subsequent stroke risk. Additionally, diminished LA deformation during AF correlates with the presence of LA blood stasis. Given that endothelial function is dependent on laminar blood flow, the present study sought to investigate the effect of diminished LA deformation (during AF) on platelet reactivity and inflammation in AF patients. Patients (n=17) hospitalised with AF underwent echocardiography (while in AF) for determination of peak positive LA strain (LASp). Whole blood impedance aggregometry was used to measure extent of ADP-induced aggregation and subsequent inhibitory response to the nitric oxide (NO) donor, sodium nitroprusside. Platelet thioredoxin-interacting protein (Txnip) content was determined by immunohistochemistry. LASp tended (p=0.078) to vary inversely with CHA2DS2VASc scores. However, mediators of inflammation (C-reactive protein, Txnip) did not correlate significantly with LASp nor did extent of ADP-induced platelet aggregation or platelet NO response. These results suggest that the thrombogenic risk associated with LA stasis is independent of secondary effects on platelet aggregability or inflammation.